Involvement of Calcium-Dependent Pathway and β Subunit-Interaction in Neuronal Migration and Callosal Projection Deficits Caused by the Cav1.2 I1166T Mutation in Developing Mouse Neocortex - Nakagawa-Tamagawa, Nao; Kirino, Emi; Sugao, Kohtaroh; Nagata, Hidetaka; Tagawa, Yoshiaki (Frontiers in Neuroscience, 2021)
Introduction: Gain-of-function mutations in the L-type Ca2+ channel Cav1.2 cause Timothy syndrome (TS), a multisystem disorder associated with neurologic symptoms, including autism spectrum disorder, seizures, and intellectual disability. Cav1.2 plays key roles in neural development, and its mutation can affect brain development and connectivity through Ca2+-dependent and -independent mechanisms. Recently, a gain-of-function mutation, I1166T, in Cav1.2 was identified in patients with TS-like disorder. Its channel properties have been analyzed in vitro but in vivo effects of this mutation on brain development remain unexplored. Methods: In utero electroporation was performed on ICR mice at embryonic day 15 to express GFP, wild-type, and mutant Cav1.2 channels into cortical layer 2/3 excitatory neurons in the primary somatosensory area. The brain was fixed at postnatal days 14–16, sliced, and scanned using confocal microscopy. Neuronal migration of electroporated neurons was examined in the cortex of the electroporated hemisphere, and callosal projection was examined in the white matter and contralateral hemisphere. Results: Expression of the I1166T mutant in layer 2/3 neurons caused migration deficits in approximately 20% of electroporated neurons and almost completely diminished axonal arborization in the contralateral hemisphere. Axonal projection in the white matter was not affected. We introduced second mutations onto Cav1.2 I1166T; L745P mutation blocks Ca2+ influx through Cav1.2 channels and inhibits the Ca2+-dependent pathway, and the W440A mutation blocks the interaction of the Cav1.2 α1 subunit to the β subunit. Both second mutations recovered migration and projection. Conclusion: This study demonstrated that the Cav1.2 I1166T mutation could affect two critical steps during cerebrocortical development, migration and axonal projection, in the mouse brain. This is mediated through Ca2+-dependent pathway downstream of Cav1.2 and β subunit-interaction.